Duration Strategy For Heart Falling Patients; Policy Support, Nurse Competency Improvement, Heart Rehabilitation RSUD Karawang Districtin 2020 - Ilham Suryana; Wati Jumaiyah; Fitrian Rayasari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Heart failure can cause various complications if not treated seriously, such as pulmonary edema, impaired kidney function, and ascites. This can cause the length of stay of patients to increase. This study used a quast experimental post test control group design. The aim of this research is to find out strategies to reduce the length of stay of patients with heart failure. The number of respondents in this study were 100 patients, each of which was 50 people per group. Based on the results of the Chi-square test of applying the strategy with length of stay seen from the continuity correction, the p-value is 0.000. The p-value implies that the implementation of the strategy has a significant effect on the length of stay in heart failure patients. In addition to the p-value, an OR value of 7.534 was also obtained, which means that the implementation of the strategy has the opportunity to reduce the length of stay by 7.534 times compared to those who do not apply the strategy of decreasing hospitalization days. The right strategy in reducing the length of days of care for heart failure patients is by implementing it through policy support, increasing the competence of nurses and cardiac rehabilitation to be carried out continuously and systematically so that it can reduce the LOS of heart failure patients at the Karawang District Hospital in 2020. Keywords: length of care; policy support; competency improvement of nurses; cardiac rehabilitation ABSTRAK Penyakit gagal jantung dapat menyebabkan berbagai komplikasi apabila tidak ditangani secara serius, seperti edema paru, gangguan fungsi ginjal, dan asites. Hal ini dapat menyebabkan length of stay pasien semakin bertambah. Tujuan penelitin ini adalah untuk mengetahui strategi penurunan lama hari rawat pasien gagal jantung. Penelitian ini menggunakan desain quast experimental post test control group desain. Jumlah responden dalam penelitian ini sebanyak 100 pasien dengan jumlah masing-masing adalah 50 orang per kelompok. Berdasarkan hasil uji Chi-square penerapan strategi dengan lama rawat dilihat dari continuity correction didapatkan nilai p-value 0,000. Nilai p-value tersebut bermaksa bahwa penerapan strategi berpengaruh secara signifikan terhadap lama hari rawat pasien gagal jantung. Selain nilai p-value, didapatkan pula nilai OR 7,534 yang bermakna bahwa penerapan strategi berpeluang menurunkan lama hari rawat sebesar 7,534 kali dibandingkan dengan yang tidak menerapkan stategi penurunan hari rawat. Strategi yang tepat dalam menurunkan lama hari perawatan pasien gagal jantung yaitu dengan penerapan melalui dukungan kebijakan, peningkatan kompetensi perawat dan rehabilitasi jantung dilakukan secara berkesinambungan dan sistematis sehingga dapat menurunkan LOS pasien gagal jantung di RSUD Kabupaten Karawang Tahun 2020. Kata kunci: lama hari rawat; dukungan kebijakan; peningkatan kompetensi perawat; rehabilitasi jantung